2017
DOI: 10.1016/j.psychsport.2017.07.001
|View full text |Cite
|
Sign up to set email alerts
|

Introductory dialogue and the Köhler Effect in software-generated workout partners

Abstract: Objectives This study explored the Köhler motivation gain effect utilizing adults and software-generated partners (SGPs) during an abdominal exercise regimen and compared the type of participant-SGP introductory dialogue as a moderator. The Köhler effect applies interdependent team dynamics in which group performance is dependent upon the weaker member. The third objective was to examine if this motivation paradigm would result in adverse consequences to secondary variables: exertion, enjoyment, and self-effic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…In other words, people respond socially to human-like characteristics of computers and apply social rules to their interactions when doing so 29, 30. Recent studies have successfully used SGPs in exercise-persistence tasks 31, 32, 33. Not only did the participants rate the exercise SGPs positively in terms of likability and anthropomorphic features, but the motivation gain across these sequential studies also demonstrated moderate effect sizes (Feltz et al, 31 d = 0.57; Samendinger et al, 33 d = 0.76).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In other words, people respond socially to human-like characteristics of computers and apply social rules to their interactions when doing so 29, 30. Recent studies have successfully used SGPs in exercise-persistence tasks 31, 32, 33. Not only did the participants rate the exercise SGPs positively in terms of likability and anthropomorphic features, but the motivation gain across these sequential studies also demonstrated moderate effect sizes (Feltz et al, 31 d = 0.57; Samendinger et al, 33 d = 0.76).…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have successfully used SGPs in exercise-persistence tasks 31, 32, 33. Not only did the participants rate the exercise SGPs positively in terms of likability and anthropomorphic features, but the motivation gain across these sequential studies also demonstrated moderate effect sizes (Feltz et al, 31 d = 0.57; Samendinger et al, 33 d = 0.76). These effects were similar in magnitude to those previously reported to be observed with human partners during conjunctive task groups ( g = 0.72) 17 .…”
Section: Introductionmentioning
confidence: 99%
“…K. Lee, Kiesler, & Forlizzi, 2010). One way to an exchange of spoken information is to employ a dialogue tree in exergames (Samendinger et al, 2017), which was applied in the present study. Therefore, we suggest taking advantage of group dynamics with SGPs in commercial exergames (e.g., Wii Fit, PS-2’s EyeToy: Kinetic) or any health game because players can even interact with SGPs in exergame play.…”
Section: Discussionmentioning
confidence: 99%
“…The Köhler effect occurs in group tasks when the less capable partner of the group shows greater motivation in terms of effort, relative to his/her individual performance (Kerr & Hertel, 2011; and see Weber & Hertel, 2007 for a meta-analysis). The Köhler effect is considered as one of few group dynamics capable of realizing motivation gains (Samendinger et al, 2017). These motivation gains occur in conjunctive tasks, in which the performance of the group is judged by the inferior partner’s performance.…”
mentioning
confidence: 99%
“…The setting can range from standard exercise classes in which members have little prior knowledge of each other and little interaction during the classes to groups in which group dynamic principles have been used to enhance group perceptions and cohesion (Burke, Carron, Eys, Ntoumanis, & Estabrooks, 2006). However, regardless of the nature of the exercise setting, group constructs appear to play an important role with respect to cohesion (Spink & Carron, 1994), Köhler effect (Samendinger et al, 2017), social norms (Priebe & Spink, 2015), leadership (Crozier & Spink, 2018), and groupness (Crozier, Martin, & Spink, in press) as they relate to group maintenance and member behavior. Given that psychotherapy groups are likely more similar to minimal than true groups, it could be posited that there might be a more direct transfer from findings in the exercise setting to psychotherapy groups.…”
Section: Unique Characteristics Of the Sports And Exercise Settingmentioning
confidence: 99%